Effect of Nicotinic Acid on Sperm Characteristic and Oocyte Development after In Vitro Fertilization using Cryopreserved Boar Semen - Yu-Jin Kim; Sang-Hee Lee; Yeon-Ju Lee; Hae-In Oh; Hee-Tae Cheong; Boo-Keun Yang; Seunghyung Lee; Choon-Keun Park (The Korean Society of Animal Reproduction and Biotechnology, 2015)
The objective of this study was to investigate the efficiency of nicotinic acid on sperm cryosurvival and fertilization ability in frozen-thawed boar semen. Boar semen was collected by glove-hand method and was frozen using freezing solution treated to 0, 5, 10 and 20 mM of nicotinic acid. The frozen sperm for sperm characteristic analysis was thawed such as viability, acrosome reaction, and mitochondrial integrity. The frozen-thawed sperm was estimated by SYBR14/PI double staining for viability, FITC-PNA/PI double staining for acrosome reaction and Rhodamine123/PI double staining for mitochondrial integrity using a flow cytometry. The embryo was estimated in vitro development and DCFDA staining for reactive oxygen species assessment. As results, frozen-thawed sperm viability was significantly higher in 5 and 10 mM (61.1 ± 1.5%, 64.7 ± 2.0%) of nicotinic acid than other groups (0 mM, 52.1 ± 2.3%; 20 mM, 47.8 ± 5.1%, P<0.05). The live sperm with acrosome reaction was significantly higher in 5 and 10 mM of nicotinic acid (26.1 ± 1.8%, 24.9 ± 1.5%) than other groups (0 mM, 35.3 ± 0.8%; 20 mM, 36.5 ± 1.9%, P<0.05). The live sperm with mitochondrial integrity was significantly higher in 5 and 10 mM (84.2 ± 3.6%, 88.4 ± 2.3%) of nicotinic acid than other groups (0 mM, 77.3 ± 4.4%; 20 mM, 73.3 ± 3.6%, P<0.05). Blastocyst rate of in vitro development was significantly higher in 10 mM (17.0 ± 1.3%) of nicotinic acid than other groups (0 mM, 9.4 ± 0.5%; 5mM, 12.6 ± 0.8%; 20 mM, 5.0 ± 1.0%, P<0.05). Moreover, total cell number was higher in 5 and 10 mM (53.6 ± 2.9%, 57.9 ± 2.8%) of nicotinic acid than other groups (0 mM, 41.0 ± 1.4%; 20 mM, 23.2 ± 2.8%, P<0.05). Hydrogen peroxide in embryos was lower in 5 mM nicotinic acid (0.7 ± 0.1%) than other groups (0 mM, 1.0 ± 0.1%; 10mM, 0.9 ± 0.0%; 20 mM, 1.4 ± 1.0%, P<0.05). In conclusion, nicotinic acid-treated semen improves cryosurvival and quality of spermatozoa. Also, the fertilized oocytes with nicotinic acid improve quality of embryo and blastocyst formation.